Soccer as training and development tool in children participating in sports schools (Journal on studies and research of academic knowledge, 2022)
The purpose of this research was to analyze soccer as a training and development tool for children between 10 and 11 years old in three soccer schools in Asunción. The study frame of reference is based on learning and benefits that could be gained thorough this sport, and more specifically on the learning of values. The design used was observational and descriptive, through a qualitative approach, with the application of guided open questions to the players' parents, Paraguayan coaches and foreign coaches; it was applied virtually during June 2020.  Data collection was carried out through emails sent to the participants of the study. The population consisted of 9 parents (three from each school), 3 teacher coaches and 3 foreign coaches. The sample was intentional and with inclusion criteria. Results show that soccer benefits the integral development of children, inspires them to be better people every day as it contributes to the formation of values; in addition, it benefits their mental, emotional and physical health. It is concluded that both parents and coaches perceive soccer as an important space for significant learning and that it should be used as a formative tool in children's lives.
Keywords: Soccer Schools; Learning and Training; Values; Children